If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+2=-10+2x
We move all terms to the left:
x+2-(-10+2x)=0
We add all the numbers together, and all the variables
x-(2x-10)+2=0
We get rid of parentheses
x-2x+10+2=0
We add all the numbers together, and all the variables
-1x+12=0
We move all terms containing x to the left, all other terms to the right
-x=-12
x=-12/-1
x=+12
| -5(x+2)2;x=-3 | | 3u+8=26 | | 3(8+6m)=-102 | | g-0.003=-0.0017 | | 0=-401,6+39,2x+4.9x^2 | | 1y+6+4y-13=26 | | 3.5z-2.7z= | | x=(2x-9)- | | h+50.3=80.2 | | 5=m+12.5-m | | 2v+16=36 | | 7u+-10=-73 | | 6p-8=-5p+18 | | -5+w/2=-1 | | 4(1+3)=3a(2a+1) | | 32 y−7 =9 | | 56+e=450 | | 17p-8=18 | | (3+x)2=4 | | w^2+15w-225=0 | | 1,105=(x+25)13 | | 1/3x+3=26+16/8x-23 | | 15z-6=11z-50 | | 26=17p | | 12m+20=175 | | l-0.02=-0.006 | | X+27=3x-39 | | 26=2(q-72) | | 5x−4=x−2 | | s+38=-14 | | 5x−4 =x−2 | | 6+9x=69 |